Mirambo of Tanzania - Unomah, A C (Heinemann Educational Books Ltd, 1977)
Mirambo,a great military ruler established a powerful kingdom not in response to the European outsiders but to the situation in East Africa.
Keywords: Juvenile literature-Biographies-History-Tanzania-Nonfiction